2012
DOI: 10.1084/jem.20120225
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell development requires transient Wnt/β-catenin activity

Abstract: Deletion of β-catenin from mouse embryonic endothelium, but not embryonic hematopoietic cells, prevents hematopoietic differentiation; thus Wnt/β-catenin signaling is needed for emergence but not maintenance of HSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 46 publications
5
118
2
2
Order By: Relevance
“…These results place the function of Chd1 downstream of the requirement for Wnt/β-catenin activity (35) and upstream of the activation of CD45. These data indicate that the earliest definitive hematopoietic progenitors form in Chd1 mutants but fail to expand in number and instead are lost by apoptosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results place the function of Chd1 downstream of the requirement for Wnt/β-catenin activity (35) and upstream of the activation of CD45. These data indicate that the earliest definitive hematopoietic progenitors form in Chd1 mutants but fail to expand in number and instead are lost by apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…However, the low percentage of endothelial cells that differentiate into hematopoietic cells and the technical difficulty in isolating these hemogenic clusters result in limited material available for analysis. Consequently, very little is known about how the endothelial-tohematopoietic transition occurs in vivo, and only a few genes or pathways, including Runx1 (7), Gata2 (13), Notch signaling (50), and the Wnt/β-catenin pathway (35), have been implicated in this process. Our study documents that Chd1 is the first chromatin remodeler, to our knowledge, shown to be essential for the emergence of HSPCs from the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PKA-CREB signaling pathway has been explored in the context of the prostaglandin E 2 signaling pathway in zebrafish, where it promotes AGM hematopoiesis via activation of the Wnt pathway ). However, whether this pathway is conserved in the mouse is unclear, especially given conflicting reports on Wnt signaling in AGM hematopoiesis (Ruiz-Herguido et al, 2012;Chanda et al, 2013). Prostaglandin E 2 also directly activates several pathways including PI3K-AKT and ERK-MAPK, which makes it difficult to conclude that PKA-CREB is the sole mediator of the pro-hematopoietic effects of this molecule (Alfranca et al, 2006).…”
Section: Genomic Binding and Interaction Of Creb In K562 Cellsmentioning
confidence: 99%
“…Notch (Burns et al, 2005;Butko et al, 2016;Clements and Traver, 2013;Gering and Patient, 2010;Lawson et al, 2001), Bone morphogenetic protein (Bmp) (Wilkinson et al, 2009), Wnt (Goessling et al, 2009;Luis and Staal, 2009;North et al, 2007;Ruiz-Herguido et al, 2012), Shh Gering and Patient, 2005;Lawson et al, 2002;Wilkinson et al, 2009), Vegfa (Burns et al, 2005;Patient, 2005, 2010;Lawson et al, 2003), and Tgfβ (Monteiro et al, 2016) all contribute to HSC program initiation.…”
Section: Introductionmentioning
confidence: 99%